The impact of a 16-week dietary intervention with prescribed amounts of whole-grain foods on subsequent, elective whole grain consumption. - Brownlee, I; Kuznesof, SA; Moore, C; Jebb, SA; Seal, C (2013)
Previous (mainly population-based) studies have suggested the health benefits of the elective, lifelong inclusion of whole-grain foods in the diet, forming the basis for public health recommendations to increase whole grain consumption. Currently, there is limited evidence to assess how public health recommendations can best result in longer-term improvements in dietary intake. The present study aimed to assess the impact of a previous 16-week whole-grain intervention on subsequent, elective whole grain consumption in free-living individuals. Participants completed a postal FFQ 1, 6 and 12 months after the end of the whole-grain intervention study period. This FFQ included inputs for whole-grain foods commonly consumed in the UK. Whole grain consumption was significantly higher (approximately doubled) in participants who had received whole-grain foods during the intervention (P< 0.001) compared with the control group who did not receive whole-grain foods during the intervention. This increased whole grain consumption was lower than whole grain intake levels required by participants during the intervention period between 60 and 120 g whole grains/d. Aside from a significant increase (P< 0.001) in NSP consumption compared with control participants (mean increase 2-3 g/d), there were no obvious improvements to the pattern of foods of the intervention group. The results of the present study suggest that a period of direct exposure to whole-grain foods in non-habitual whole-grain food consumers may benefit subsequent, elective dietary patterns of whole grain consumption. These findings may therefore aid the development of future strategies to increase whole grain consumption for public health and/or food industry professionals.